Job satisfaction in compensation, environment, discipline, and performance: evidence from Indonesia higher education - Saputra, Pramana; Sudiro, Achmad; Irawanto, Dodi W. (MEC-J (Management and Economics Journal), 2018)
This research aims to examine the role of job satisfaction in compensation, environment, discipline, and performance in Indonesia Higher Education, exactly in State Polytechnic of Banjarmasin (POLIBAN). To examine the hypotheses and mediator variabel, this research used Partial Least Square (PLS). It found that of ten hypotheses tested, four hypeteses were negative and insignificant. In addition, the test of mediation, by PLS, also showed that Job satisfaction cannot mediate the relationship between compensation and performance. However, it can be a mediator for the relationship between environment or discipline and performance. These results confirmed and contradict to the previous studies conducted.